1989
DOI: 10.1136/gut.30.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of biliary tract disease in India: a sonographic study in adult population in Kashmir.

Abstract: SUMMARY Sonography was used to investigate the prevalence of symptomatic and silent biliary tract disease, in free living urban population in Kashmir. A randomly drawn sample of 1695 subjects aged 15 years or above was interviewed by a questionnaire. Twenty six had previous cholecystectomies, all for gall stones. Ultrasonography was carried out on 1104 (6541%). The responder rates for ultrasonography in men (64P3%) and in women (66-0%) were similar (p>02). Gall stones were detected in 49 adults. Three of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
111
6
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 13 publications
10
111
6
1
Order By: Relevance
“…The present study is a prospective analysis of clinicosonological aspects of biliary lithiasis in a service hospital. Various authors have found prevalance rate of [6][7][8]. The overall prevalence of biliary lithiasis as revealed in our study is 11.56%.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The present study is a prospective analysis of clinicosonological aspects of biliary lithiasis in a service hospital. Various authors have found prevalance rate of [6][7][8]. The overall prevalence of biliary lithiasis as revealed in our study is 11.56%.…”
Section: Discussionsupporting
confidence: 58%
“…The overall prevalence of biliary lithiasis as revealed in our study is 11.56%. World wide, almost all studies strongly correlate gallstone prevalence with advancing age and report highest prevalence in the oldest age group [6,9,10]. In contrast, our study shows maximum concentration of cases around 50 years.…”
Section: Discussioncontrasting
confidence: 58%
“…However, this trend is now showing pan India presence probably because of migration and mixing of cultures. As many as 16% and 29% of women above the age of 40-49 years and 50-59 years, respectively, had gall stones [1] . For every patient with symptomatic gallstones there are many more with asymptomatic gallstones.…”
Section: Introductionmentioning
confidence: 99%
“…However the said article does not say so. In fact in Kashmir, where cholelithiasis is reported to be rampant [2] the incidence is only 6.12 per cent of the population [3].…”
mentioning
confidence: 99%